Severe Pediatric TBI Management in a Middle-Income Country and a High-Income Country: A Comparative Assessment of Two Centers - Arango, Jorge I.; George, Laeth; Griswold, Dylan P.; Johnson, Erica D.; Suarez, Maria N.; Caquimbo, Laura D.; Molano, Milton; Echeverri, Raul A.; Rubiano, Andres M.; Adelson, P. David (Frontiers in Surgery, 2021)
Background: Traumatic brain injury (TBI) is a global public health issue with over 10 million deaths or hospitalizations each year. However, access to specialized care is dependent on institutional resources and public health policy. Phoenix Children's Hospital USA (PCH) and the Neiva University Hospital, Colombia (NUH) compared the management and outcomes of pediatric patients with severe TBI over 5 years to establish differences between outcomes of patients managed in countries of varying resources availability. Methods: We conducted a retrospective review of individuals between 0 and 17 years of age, with a diagnosis of severe TBI and admitted to PCH and NUH between 2010 and 2015. Data collected included Glasgow coma scores, intensive care unit monitoring, and Glasgow outcome scores. Pearson Chi-square, Fisher exact, T-test, or Wilcoxon-rank sum test was used to compare outcomes. Results: One hundred and one subjects met the inclusion criteria. NUH employed intracranial pressure monitoring less frequently than PCH (p = 0.000), but surgical decompression and subdural evacuation were higher at PCH (p = 0.031 and p = 0.003). Mortality rates were similar between the institutions (15% PCH, 17% NUH) as were functional outcomes (52% PCH, 54% NUH). Conclusions: Differences between centers included time to specialized care and utilization of monitoring. No significant differences were evidenced in survival and the overall functional outcomes.